Collagen-induced arthritis and imiquimod-induced psoriasis develop independently of interleukin-33. Issue 1 (December 2016) - Athari, Sara; Poirier, Elodie; Biton, Jérôme; Semerano, Luca; Hervé, Roxane; Raffaillac, Aurélie; Lemeiter, Delphine; Herbelin, André; Girard, Jean-Philippe; Caux, Frédéric; Boissier, Marie-Christophe; Bessis, Natacha
Abstract Background Interleukin (IL)-33 is a dual cytokine with both an alarmin role and a T helper 2 cell (Th2)-like inducing effect. It is involved in the pathogenesis of rheumatoid arthritis (RA) and its models; we recently demonstrated that exogenous IL-33 could inhibit collagen-induced arthritis (CIA) in C57BL/6 mice. However, its pathophysiological role in RA is unclear. Indeed, mice deficient in the IL-33 receptor ST2 show reduced susceptibility to arthritis, and the disease is not modified in IL-33-deficient mice. We examined the immune response in wild-type (WT) and IL-33-deficient mice with CIA. To further understand the role of endogenous IL-33 in inflammatory diseases, we studied its role in a skin psoriasis model. Mice on a C57BL/6 background were deficient inIL-33 but expressed lacZ under the IL-33 promoter. Therefore, IL-33 promotor activity could be analyzed by lacZ detection and IL-33 gene expression was analyzed by X-Gal staining in various mice compartments. Frequencies of CD4+ FoxP3+ regulatory T cells (Tregs) and Th1 and Th17 cells were evaluated by flow cytometry in WT and IL-33-/- mice. Bone resorption was studied by evaluating osteoclast activity on a synthetic mineral matrix. Psoriasis-like dermatitis was induced by application of imiquimod to the skin of mice. Results Severity of CIA was similar in IL-33-/- and WT littermates. Joints of IL-33-/- mice with CIA showed IL-33 promotor activity. In mice with CIA, frequencies of Tregs, Th1 and Th17 in the spleen or lymph nodes did not differ between the genotypes; osteoclast activity was higher but not significantly in IL-33-/- than WT mice. Psoriasis development did not differ between the genotypes. Conclusions Despite its expression in the synovium of arthritic mice and normal keratinocytes, IL-33 is not required for CIA development in arthritis or psoriasis. Its absence does not induce a T cell shift toward Th1, Th17 or Treg subpopulations. Altogether, these data and our previous ones, showing that exogenous IL-33 can almost completely inhibit CIA development, suggest that this cytokine is not crucial for development of chronic inflammation. Studies of RA patients are needed to determine whether treatment targeting the IL-33/ST2 axis would be effective.